Keanekaragaman Jenis Burung di Kawasan Kampus Universitas Udayana, Bukit Jimbaran, Bali - Sharon, Michelle Angelina; Sumbawati, Ni Kadek Aryani; Andani, Firman; Zaetuna, Hanifa Laila; Wijaya, I Made Saka; Yuni, Luh Putu Eswaryanti Kusuma (Bumi Lestari, 2024)
Birds are an important component of balancing ecosystems and have a reciprocal relationship and close dependence to their environment. The high number of bird species found can indicate the ecological role of the environment, either for finding food and shelter, or for nesting and breeding areas. Udayana University Bukit Jimbaran Campus, with a total land area of ??27,649 ha, still has plenty of green area. This condition provides great potential as habitat for various bird species. This study aims to identify the bird species found in Udayana University Bukit Jimbaran campus area. The method used was the point count method at 11 observation points that was determined by purposive sampling. The indices calculated were the diversity, uniformity, dominance, and relative abundance. From this study, 30 bird species from 18 families were recorded with a total of 571 individuals scattered at each observation point. Based on the calculated indices, the diversity of bird species in Bukit Jimbaran Udayana University campus area was considered as moderate, with a stable species distribution, and low dominance (no species dominates). Keywords : abundance, birds, diversity, dominance, evenness